2016
DOI: 10.1021/acsnano.6b00888
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Alveolus-Like Nanovesicle Assembly with Metal-Encapsulated Hollow Zeolite Nanocrystals

Abstract: Inspired by the vesicular structure of alveolus which has a porous nanovesicle structure facilitating the transport of oxygen and carbon dioxide, we designed a hollow nanovesicle assembly with metal-encapsulated hollow zeolite that would enhance diffusion of reactants/products and inhibit sintering and leaching of active metals. This zeolitic nanovesicle has been successfully synthesized by a strategy which involves a one-pot hydrothermal synthesis of hollow assembly of metal-containing solid zeolite crystals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(52 citation statements)
references
References 87 publications
3
49
0
Order By: Relevance
“…By applying as both the anode and cathode, the catalyst required only an overall potential of 1.64 V to drive the current density of 10 mA cm −2 for the water splitting, and showed superior stability in the continuous 36 h test. Dai et al reported Fe 2 O 3 encapsulated hierarchical hollow ZSM‐5 nanospheres by the assembly of hollow alveolus‐like nanovesicles via a one‐pot hydrothermal method . Structural characterizations demonstrated that 3–4 nm Fe 2 O 3 NPs were homogeneously dispersed in the thermally stable (up to 800 °C) porous zeolite assembly with an ≈350 nm cavity, 5–17 nm mesoporous interparticle shell, and 0.4–0.6 nm microporous particle walls.…”
Section: Insight Into Hollow Nanomaterials As a Nanoreactor In Spatiamentioning
confidence: 99%
“…By applying as both the anode and cathode, the catalyst required only an overall potential of 1.64 V to drive the current density of 10 mA cm −2 for the water splitting, and showed superior stability in the continuous 36 h test. Dai et al reported Fe 2 O 3 encapsulated hierarchical hollow ZSM‐5 nanospheres by the assembly of hollow alveolus‐like nanovesicles via a one‐pot hydrothermal method . Structural characterizations demonstrated that 3–4 nm Fe 2 O 3 NPs were homogeneously dispersed in the thermally stable (up to 800 °C) porous zeolite assembly with an ≈350 nm cavity, 5–17 nm mesoporous interparticle shell, and 0.4–0.6 nm microporous particle walls.…”
Section: Insight Into Hollow Nanomaterials As a Nanoreactor In Spatiamentioning
confidence: 99%
“…55 ppm, attributed to the tetrahedrally coordinated framework Al species (FAL), while the resonances at ca. 0 ppm are very weak, which is usually assigned to the octahedrally coordinated extra‐framework Al species (EFAL) . These results demonstrate that almost all Al atoms in HSZs‐ 5 and HSZs‐ 48 are isomorphous substituted for Si atoms in Silicalite‐1 frameworks.…”
Section: Resultsmentioning
confidence: 84%
“…The specific surface area and total pore volume including meso‐ and macropore volumes were decreased slightly after desilication, but increased markedly after dealumination, this indicated that dealuminization has a more significant effect for textural properties than desilication for the parent HZSM‐5. For HZSM‐5‐0.09 M‐1‐M, the change of specific surface area and pore volume was not obvious after surface‐passivation by liquid phase deposition, but increased obviously after hydrothermal treatment, this might be due to the silicate oligomers within catalyst crystal was dissolved in the process of hydrothermal treatment and then in the template agent on the crystal surface under the action of secondary crystallization, it could also be demonstrated in Figure , the relative crystallinity from 73 % of HZSM‐5‐0.09 M‐1‐M to 97 % of Si/HZSM‐5‐0.09 M‐1M T .…”
Section: Resultsmentioning
confidence: 93%